Programming Fluorogenic DNA Probes for Rapid Detection of Steroids. (1st June 2021) - Ebrahimi, Sasha B.; Samanta, Devleena; Partridge, Benjamin E.; Kusmierz, Caroline D.; Cheng, Ho Fung; Grigorescu, Arabela A.; Chávez, Jorge L.; Mirau, Peter A.; Mirkin, Chad A.
Abstract: The ability of aptamers to recognize a variety of different molecules has fueled their emergence as recognition agents to probe complex media and cells. Many detection strategies require aptamer binding to its target to result in a dramatic change in structure, typically from an unfolded to a folded state. Here, we report a strategy based on forced intercalation (FIT) that increases the scope of aptamer recognition by transducing subtle changes in aptamer structures into fluorescent readouts. By screening a library of green‐fluorescent FIT‐aptamers whose design is guided by computational modeling, we could identify hits that sense steroids like dehydroepiandrosterone sulfate (DHEAS) down to 1.3 μM with no loss in binding affinity compared to the unmodified aptamer. This enabled us to study DHEAS in clinical serum samples with several advantages over gold standard methods, including rapid readout (<30 min), simple instrumentation (plate‐reader), and low sample volumes (10 μL). Abstract : Aptamers based on forced intercalation (FIT) were developed to detect steroids such as dehydroepiandrosterone sulfate in clinical human serum samples. These FIT‐aptamers offer several advantages over gold standard methods, including rapid readout (<30 min), simple instrumentation (plate‐reader), and low sample volumes (10 μL).